Awareness of public in Kuantan on the roles and services provided by an audiologist - Azrin, Nor Azri; Othman, Nur Ain; Tukiran, Nur Hanisah (IIUM Medical Journal Malaysia, 2016)
Introduction: Prevalence of disabling hearing loss among Malaysians is 5%, according to Malaysia’s Health Survey. The need for audiological service is clear. Despite the urgencies in hearing-related health issues, there is not much known about public awareness of the audiologist’s role and services especially in Kuantan. This current study aims to explore this matter. Methods: Self-administered questionnaires consisting 2 sections were distributed randomly in public in Kuantan. Section A comprises of participants’ sociodemographic information (i.e. gender, race, age, occupation, and level of education). Section B consists of Part a: Familiarity with Audiological Services, Part b: Knowledge on Role and Services of Audiologists, and Part c: Source of Information. 56 respondents were involved. Results: 66.07% of subjects (n=37) claimed they knew about the audiologist existence in Malaysia and 33.93% (n=19) claimed otherwise. There is no significant association between sociodemographic information with the awareness on audiologist existence and also the knowledge that respondents were regarding audiologist role and services. There is a significant association between participants' awareness on the audiologist existence in Malaysia with their familiarity with audiologists (p-value = 0.006). There is also a significant association between the responder awareness with their knowledge on audiologist role and services (p-value = 0.006). However, there is no association between respondents’ familiarity with audiologists and their knowledge on audiologist role and services. Conclusions: Public awareness on audiologists role and services in Kuantan is fair.